Best Android apps the guide for discriminating downloaders - Hendrickson, Mike (O'Reilly Media, 2010)
"You can choose from thousands of apps to make your Android device do just about anything you can think of -- and probably a few things you'd never imagine. There are so many Android apps available, in fact, that it's been difficult to find the best of the bunch -- until now. Best Android Apps leads you beyond the titles in Android Market's 'Top Paid' and 'Top Free' bins to showcase apps that will truly delight, empower, and entertain you. The authors have tested and handpicked more than 200 apps and games, each listed with a description and details highlighting the app's valuable tips and special features. Flip through the book to browse their suggestions, or head directly to the category of your choice to find the best apps to use at work, on the town, at play, at home, or on the road."--Publisher's description.
Includes bibliographical references and index. - Print version record
Keywords: Android (Electronic resource); Smartphones -- Programming; Application software -- Evaluation; Téléphones intelligents; Programmation; Logiciels d'application; Évaluation; COMPUTERS; Hardware; Handheld Devices; Smartphones; Programming; Application software; Evaluation